Religious Activity-Based School Culture Program Implementation In MA Paradigma Palembang - Hardi Fardiansyah; Indah Rahayu; Ida Bagus Benny Surya Adi Pramana; Halimatun Syakdiah; Muhamad Yahya (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The background of this research is that the religious culture of the school is essentially the embodiment of the values of religious teachings as a culture of behaviour and an organizational culture that all school members follow. This needs to be done so that Islamic religious discounts are always reflected in the daily conduct of all school members, especially students, and they can be calm in dealing with negative cultures in their environment. The method in this research is descriptive research with a qualitative approach. Data collection techniques using observation, interviews, and documentation. The study results a show that implementing The religious culture contained in MA Paradigma is a set of religious values, namely the mandatory tradition of wearing the hijab, the habit of shaking hands with teachers when entering the school gate, the practice of reading the Koran and short letters, muhadhoroh, and performing midday prayers in congregation. The supporting factors are 1) Islamic-based schools; 2) Morals to teachers and elders; 3) Parents or guardians of students who can be invited to work together; 4) Having a broad understanding and view of Islam; and 5) Supervising teachers who participate directly in activities. The inhibiting factors are 1) the schedule of religious activities that collide with the teaching and learning schedule, 2) Students who are still negligent in participating in activities, and 3) Media information.